Ireland : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report, 2016)
This paper discusses key findings of the Financial System Stability Assessment for Ireland. The Irish financial system has strengthened significantly since the crisis and undergone major structural changes. Important vulnerabilities in the banking system relate to the real-estate sector, some parts of the corporate sector, the sovereign, and funding in pound sterling. Pockets of weakness remain, notably among highly leveraged households and smaller domestic firms. Over the medium term, technological innovations and shifts in competitive pressures will throw up challenges to the profitability of both banks and nonbank financial institutions. The U.K. vote to leave the EU is also very likely to have negative effects on the Irish financial system.